Downregulation of TBXAS1 in an iron‐induced malignant mesothelioma model. Issue 10 (19th September 2015) - Minami, Daisuke; Takigawa, Nagio; Kato, Yuka; Kudo, Kenichiro; Isozaki, Hideko; Hashida, Shinsuke; Harada, Daijiro; Ochi, Nobuaki; Fujii, Masanori; Kubo, Toshio; Ohashi, Kadoaki; Sato, Akiko; et al.
Abstract : Malignant mesothelioma is an aggressive and therapy‐resistant neoplasm arising from mesothelial cells. Evidence suggests that the major pathology associated with asbestos‐induced mesothelioma is local iron overload. In the present study, we induced iron‐induced mesothelioma in rats based on previous reports. Ten Wistar rats were given ferric saccharate and nitrilotriacetate i.p. for 5 days a week. Five of the ten rats exhibited widespread mesotheliomas in the peritoneum and tunica vaginalis. The tumor cells showed positive immunostaining for calretinin, wilms tumor‐1, podoplanin and the oxidative DNA marker 8‐hydroxy‐2′‐deoxyguanosine. In three of the five rats with mesothelioma, array‐based comparative genomic hybridization analysis identified a common chromosomal deletion mapped to the chromosomal 4q31 locus, which encompasses the TBXAS1 gene. Downregulation of the TBXAS1 gene was confirmed using quantitative PCR. TBXAS1 gene expression was also reduced in three of four human malignant pleural mesothelioma cell lines compared with normal bronchial epithelial cells. Immunohistochemistry revealed that TBXAS1 expression was weakly positive and positive in five and three out of eight human malignant mesothelioma samples, respectively. In conclusion, TBXAS1 gene expression was downregulated in rats with iron‐induced mesothelioma. The relationship between iron overload and TBXAS1 downregulation should be pursued further. Abstract : Evidence suggests that the major pathology associated with asbestos‐induced mesothelioma is local iron overload. Here, we first confirmed the iron‐induced mesothelioma rat model and then examined the entire rat genome using array‐based comparative genomic hybridization (CGH). CGH identified a common chromosomal deletion mapped to the chromosomal 4q31 locus, which encompasses the TBXAS1 gene. Finally, we evaluated whether the results of the CGH analysis could be extrapolated to human mesothelioma cell lines and clinical samples.